The creation of competitive cities in South Africa: the case of the West Rand vision 2016 - Thwala, Nompumelelo Q. (My University, 2015)
The advent of democracy opened avenues for South Africa’s integration into the global economy. The international influences of governance and political economy have since transcended into the South African public management and its economic policies. The implications of this approach have led to the transformation of the local government sphere as an interfacing agent for service delivery, economic development and promoting democracy. Therefore, consolidation of municipalities towards becoming competitive cities lies on the justification that amalgamation can yield improvement in service delivery, redressing socio-economic and spatial disparities as well as improving economic growth. Using the West Rand district case study, it emerges that competitive cities require certain features of competitiveness ranging from sound infrastructure development, inclination to innovation, efficient governance, the ability to attract relevant labour, indigenous markets and the quality of life. However, the upsurge of creating competitive cities in South Africa is not purely for economic reasons but also political and developmental justifications. Against these features, the West Rand district possesses strategic strengths in natural endowments, governance, and a potential human capital. However, an innovation agenda for varied economic sectors, information technology and for building strategic networks must be developed in order to meet the long term vision. The report suggests that collaborative planning can be useful in building consensus and bringing on board the marginalised groups into decision making. Together with equity planning, it is considered as a guide for implementing redistributive justice as one of the objectives for amalgamation. Also, spatial reform towards a competitive region is proposed through strategic spatial planning approach to uphold democratic principles in planning for the district. The analysis leads to the conclusion that the amalgamation process is geared towards establishing a competitive West Rand region as a means of galvanising economic growth. However, the realities of service delivery challenges and a fragile economic base suggest that the mergers should also aim to enhance social justice and a redistributive developmental agenda.
A research report submitted to the Faculty of Engineering and the Built Environment, of the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Development Planning
Keywords: Cities--South Africa; Urban development--South Africa; City planning--South Africa